Compositional Analysis of Glycyrrhiza uralensis, G. inflata, and G. glabra after Honey Processing, and the Cardioprotective Effects in Zebrafish Embryos - Wang, Jiayi; Wang, Wenxin; Liu, Binghan; Fan, Xiaoyu; Liu, Shucen; Yang, Guangchao; Liu, Jining; Lu, Tulin; Chen, Lihong (Planta Medica, 2025)
The “Shang Han Lun” indicates that honey-processed licorice protects the heart better than raw licorice. Ten major constituents in honey-processed licorice samples were quantified. Protective effects of honey-processed licorices against doxorubicin-induced cardiotoxicity were assessed in zebrafish larvae. Network pharmacology analysis based on the ten target constituents was conducted. Results showed glabridin was lowest in honey-processed Gg, while total content of six components (such as liquiritin) was highest in honey-processed Gu, followed by honey-processed Gi, and lowest in honey-processed Gg. Pharmacological results indicated that honey-processed Gu and Gi significantly improved doxorubicin-induced abnormal pericardial edema and increased venous sinus-arterial bulb distance in larvae. The pericardial area was reduced by 23% and 20%, respectively compared to the model group, and the distances reduced to 81% and 83.3% of the model group, respectively. Although improvements in pericardial edema were rare in the honey-processed Gg group, it reversed venous sinus-arterial bulb distance increase. These results indicate that honey-processed Gu and honey-processed Gi can significantly protect zebrafish embryos against the effects of doxorubicin-induced cardiotoxicity, namely, abnormal heart rate, pericardial edema, and elongation of the venous sinus-arterial bulb distance, whereas honey-processed Gg can only significantly reverse the doxorubicin-induced increase in the venous sinus-arterial bulb distance. Network pharmacology analysis predicted that these constituents have potential for the treatment of metabolic abnormalities and cellular senescence related diseases caused by reactive oxygen species induction, linking to Rap1 pathways. Honey-processed Gu and honey-processed Gi had stronger cardioprotective effects on zebrafish embryos than honey-processed Gg possibly because of differences in composition.
Keywords: licorice from three origins; honey-processed licorice; compositional analysis; cardioprotective effects; Network pharmacology